2010
DOI: 10.1002/pmic.201000260
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of the thermodynamic and kinetic stabilities of SH3 domains on their aggregation inside bacteria

Abstract: The formation of insoluble deposits by globular proteins underlies the onset of many human diseases. Recent studies suggest a relationship between the thermodynamic stability of proteins and their in vivo aggregation. However, it has been argued that, in the cell, the occurrence of irreversible aggregation might shift the system from equilibrium, in such a way that it could be the rate of unfolding and associated kinetic stability instead of the conformational stability that controls protein deposition. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…1a) is provided by considering the correlation that was recently reported between protein aggregation rates and mRNA expression levels, which arises as a consequence of the stringent requirement for proteins to remain soluble in order to function at the concentrations at which they are expressed in the cell. 17,[29][30][31][32][33] On the basis of this observation, we demonstrated that it is possible to estimate the solubility of recombinant human proteins in E. coli from the corresponding maximal mRNA expression levels. 20 Here, we used this approach to provide an alternative prediction of the solubility scores provided by Niwa et al 19 finding a very high correlation (Fig.…”
mentioning
confidence: 94%
“…1a) is provided by considering the correlation that was recently reported between protein aggregation rates and mRNA expression levels, which arises as a consequence of the stringent requirement for proteins to remain soluble in order to function at the concentrations at which they are expressed in the cell. 17,[29][30][31][32][33] On the basis of this observation, we demonstrated that it is possible to estimate the solubility of recombinant human proteins in E. coli from the corresponding maximal mRNA expression levels. 20 Here, we used this approach to provide an alternative prediction of the solubility scores provided by Niwa et al 19 finding a very high correlation (Fig.…”
mentioning
confidence: 94%
“…Because protein aggregation requires at least local backbone fluctuations and in many cases partial unfolding (12,14), the deposition propensity of globular proteins appears to be linked to their thermodynamic and/or kinetic stability (10), in such a way that mutations or environmental conditions that destabilize the native structure or increase unfolding rates are associated to pathological phenotypes in several protein models (6,24). This could be one of the underlying reasons why proteins that function in harsh environments, such as the extracellular space, have evolved disulfide bonds (48).…”
Section: Introductionmentioning
confidence: 99%
“…This has allowed the development of a set of algorithms able to predict aggregation-prone regions in protein sequences as well as the overall aggregation propensity of polypeptides (Castillo et al, 2010; Hamodrakas, 2011). Several of these programs are well suited for the analysis of large protein sets, among them AGGRESCAN, an algorithm previously developed by our group (Conchillo-Sole et al, 2007; de Groot et al, 2012), which displays a high power to predict in vivo protein aggregation (Belli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%